Meningkatkan Kemampuan Menggosok Gigi melalui Media Audio Visual bagi Siswa Tunagrahita Ringan (Single Subject Research Kelas VI di SLB Al-Hidayah Padang) - Afrianti KM, Endang; Damri, Damri (ACIECE, 2019)
This research begins with the problem in SLB Al-Hidayah Padang, a child with mild mentalretardet children. brushing toothbrush has not mastered skills. This is seen when Researchers do observations and found that children still do not understand how the steps and how to brush teeth correctly.This research used experimental approach, single subject research (SSR, with ABA design, a data analysis technique used graphic visual analysis. The subject of this research is a children with mild mental retardet children. The target behavior in this study is the child can perform steps to brush teeth properly. Measurement of variables by using the percentage of the number of items of grains of the instrument. The results Showed that children's skills in brushing teeth Increased. Seen at baseline condition (A1) the which is done four times observation percentage Obtained by the child is still low, at intervention condition (B) with eight times observation, the percentage Obtained by child increase is from the initial condition, at condition of baseline A2 conducted five observation times the percentage of correct tooth brushing measures increases from the initial ability. Based on the data Reviews These show that, the audio vicual brushing toothbrush can improve the skills of children with mild retardet children